ISOTHERMAL OXIDATION STUDY OF FE-20NI-6AL-14CR-1.8TI-0.02Y0.2C-3.2W (WT.%) ALUMINA FORMING AUSTENITIC STAINLESS STEEL AT 800, 900, AND 1000 ?C - Adindanestya Putri, Bianca
National electricity consumption shows an increase along with the changes of people's lifestyles. Steam temperature of modern power plants range from 600 to 650oC. An increase in operation temperature becomes 720 to 760oC is possible to produce 50% thermal efficiency of the PLTU. According to the thermodynamics principle, the efficiency of boilers in PLTU facilities can be increased by increasing the temperature and vapor pressure. Therefore, we need an alloy that can meet the operating conditions. Construction materials for combustion in power plants generally use Ni-based superalloys. However, the expensive price of nickel become a problem that makes it less efficient to be applied for power plant construction material. As an alternative to overcome this problem, an alumina forming austenitic stainless steel (AFA-SS) alloy was developed. In this study, AFA-SS with the chemical composition of Fe-20Ni-6Al-14Cr-1,8Ti-0,02Y-0,2C-3.2W wt.% (AFAm) were examined by isothermal oxidation test at temperatures of 800, 900, and 1000 ?C, for 2, 20, 50, and 100 hours. A series of experiments were carried out to study the oxidation behavior of AFAm alloys. The experiment begun with the making of AFA-m alloys sample by melting all elements become one button. The experiment was continued by homogenizing the as cast sample. The homogenized sample was then analyzed for its microstructure using optical microscope (OM) and prepared to be tested for isothermal oxidation test at temperature variations of 800, 900, and 1000 ?C with isothermal testing time for 2, 20, 50, and 100 hours respectively, using tube furnace. The samples were then weighed. The samples from isothermal oxidation test with a variation of 2 hours and 100 hours from each test temperature were analyzed using X-ray diffraction (XRD) and scanning electron microscope (SEM) - energy dispersive spectroscopy (EDS). The hardness test was carried out on samples as homogenized and samples with 100 hours of exposure. The results showed that the AFA-m alloy had an Fe-?, B2-NiAl matrix, TiC carbide matrix, and Laves phase. The hardness of as homogenized AFA-m is 365.7 Hv and decreases along with the increase of the operating temperature. The smallest hardness is obtained in the isothermal oxidation sample with the test temperature of 1000 ?C and 100 hours test time, which is equal to 333.95 Hv. The compounds formed on the metal surfaces are Al2O3, Cr2O3, Fe3O4, Fe2O3. The main protective oxide of the AFA alloy is Al2O3, with the most protective condition is at testing temperature of 800 ?C. Oxidation rate kinetics of AFA-m alloy complies to logaritmic rate law, indicating that the oxide formed is thin, slow growing, and protective.